Digital Marketing Communication Activities on Online Magazine Gettinlow - Teguh, Monika; Dumais, Mohamad Arvel Omar; Wijaya, Claudia Theresia; Torsten, Pafgett; Vera, Awada (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The shift in lifestyle and the increasing use of gadgets and the internet has also changed the pattern of media consumption in society. Many people are starting to switch from printed media to web-based electronic media. Magazines are no exception. Many magazines are now converting their print format to digital format. In the face of this change, magazine managers must think of creative ways to keep getting readers who will ultimately maintain their existence. One of the online magazines in Indonesia that focuses on automotive, titled, Gettinlow, also competes in the online media industry. In managing this online magazine, the Gettinlow team has recorded 9 million page viewers and 1.8 million sessions in Indonesia until 2020. This is inseparable from their digital marketing communication efforts. Therefore, this study aims to describe the implementation of digital marketing communication from Gettinlow online magazine. This research contributes to the science of marketing communications, especially in digital marketing communications. Novelty in this study shows how digital marketing communications are used in marketing mass media products, especially online magazines. Hopefully, this research can add to the study of marketing communication for online media, which still needs to be discussed. This research will use descriptive qualitative research, with interview data collection methods and document studies. The results of this study include digital marketing communication activities carried out by the Gettinlow team to retain readers and advertisers. Some activities include social media marketing, search engine optimization, and digital public relations. These activities have proven successful in increasing Gettinlow's website traffic, increasing interaction, and bringing in advertisers. Therefore, these activities can become best practices that similar companies also study.